Sistem Pewarisan Adat Lampung Pepadun Ditinjau Dari Perspektif Keadilan Dalam Tafsir Al Mishbah - Haris, Abdul; Amanda, Nuresa Divani (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The indigenous people of Lampung Pepadun adhere to the majority inheritance system, namely the ownership of inheritance property that is given to only one heir, namely the eldest son or balancer. In addition to ownership rights, they are also charged with the obligation to guard, utilize, and preserve the property, as well as bear and meet the needs of their other siblings. The objectives of this study are: 1) To find out how the Lampung Pepadun customary inheritance system is, and 2) To find out how the inheritance system is reviewed from the concept of justice in Tafsir Al Mishbah by Quraish Shihab. This research is included in the type of empirical legal research because the data used are directly sourced from the results of observations and direct interviews with informants. The approach used is a sociological juridical approach used to analyze how a law affects society and how reactions and interactions occur when a norm works in society. The two conclusions that were drawn were First, in the Lampung Pepadun customary inheritance system, the inheritance is divided into a bodel given to the balancer and a sesan given to the daughter, while the other boys get a share of the benefits based on the approval of the balancer. Second, this inheritance system does not contradict the concept of justice according to Tafsir Al Mishbah, because the distribution of inheritance has taken into account the needs of each individual, all heirs also have the opportunity to enjoy the inheritance of the heirs.